The Role of Healthcare Professionals in Implementing Health Promotion for Hypertension Prevention: A Qualitative Study - Muhammad Ilyas; Sarifudin Andi Latif (PT. Nasyah Medika Care, 2024)
Background: Hypertension remains one of the leading causes of morbidity and mortality worldwide and represents a major public health challenge in Indonesia. Despite the implementation of various health promotion programs at the primary healthcare level, hypertension prevention remains suboptimal, particularly in rural areas where community participation, health literacy, and access to preventive services are limited. Healthcare professionals play a crucial role in promoting healthy behaviors; however, evidence regarding their experiences and perspectives in implementing health promotion is still limited. Research Objective: This study aimed to explore the role of healthcare professionals in implementing health promotion for hypertension prevention in Primary Healthcare Centers in Jeneponto Regency, South Sulawesi, Indonesia. Methods: A qualitative study with a phenomenological approach was conducted between January and March 2026. Fifteen healthcare professionals, including physicians, nurses, public health officers, nutritionists, and health promotion officers, were purposively recruited. Data were collected through semi-structured in-depth interviews and analyzed using Braun and Clarke's thematic analysis supported by NVivo 14. Results: Five major themes emerged from the analysis: (1) healthcare professionals as health educators; (2) community participation as a determinant of program success; (3) barriers to implementing health promotion, including limited human resources, heavy workloads, and low public awareness; (4) the importance of culturally appropriate communication in promoting behavioral change; and (5) strengthening community-based health promotion through multisectoral collaboration and digital health strategies. Participants emphasized that sustainable hypertension prevention requires continuous education, community empowerment, and institutional support. Conclusion: Healthcare professionals play indispensable roles in hypertension prevention through education, counseling, advocacy, and community empowerment. Strengthening healthcare capacity, enhancing community participation, improving communication strategies, and fostering multisectoral collaboration are essential for developing effective and sustainable hypertension prevention programs at the primary healthcare level. Keywords: Hypertension Prevention; Health Promotion; Healthcare Professionals; Qualitative Study; Primary Healthcare.